2011
DOI: 10.1007/s11250-011-9981-3
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of bovine trypanosomosis in three villages of Metekel zone, Northwest Ethiopia

Abstract: The study was carried out to assess the economic burden of trypanosomosis in three villages of the Metekel zone in 2009. The disease was found to cause substantial economic losses through cattle mortality, drug purchase, and draft power loss of infected oxen. The farmers in the area were spending a significantly (p < 0.05) higher amount of money for the treatment of trypanosomosis than all other diseases combined. The overall mortality rate of cattle due to trypanosomosis was 4.4%. The mortality was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
21
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 14 publications
10
21
3
Order By: Relevance
“…G. tachinoides was the only species found in all the study areas. This result coincides with Mekuria and Gadissa (2011) and Tesfaye et al (2012) who revealed that G .tachinoides was the only riverine species found in Metekel zone. This could be due to the natural condition of the study areas where huge forest galleries with long river basins are favorable for this species (Pollock 1982a).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…G. tachinoides was the only species found in all the study areas. This result coincides with Mekuria and Gadissa (2011) and Tesfaye et al (2012) who revealed that G .tachinoides was the only riverine species found in Metekel zone. This could be due to the natural condition of the study areas where huge forest galleries with long river basins are favorable for this species (Pollock 1982a).…”
Section: Discussionsupporting
confidence: 91%
“…Metekel zone, one of the tsetse-infested areas, is the place where the disease has been serious for the local community affecting farm activities through reducing draught power of oxen, losses of milk, meat, growth, and finally killing of infected animals (Tesfaye et al 2012). The zone had shortage of animal health professionals so that farmers treated their animals themselves with not enough understanding of drug management which leads to drug resistance development (Afewerk et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The survey showed that trypanosomosis accounted for 2.0% to 2.8% mortality in cattle, goats and sheep. This is lower than the 6.6% and 4.4% mortality rates in cattle reports by Tesfaye et al (2011) in southern rift valley and Northwest Ethiopia. The differences could be due to the knowledge of disease management by farmers in Kachia and Saminaka.…”
Section: Discussioncontrasting
confidence: 58%
“…The values were estimated based on a review of longitudinal and cross-sectional studies comparing the productivity observed in infected and uninfected individual cattle or whole herds, under conditions of both high and low trypanosomiasis challenge (see Section 2.3.3). The effects of trypanosomiasis treatment on performance were estimated based on a review of longitudinal and cross-sectional studies comparing the productivity observed in infected and uninfected individual cattle or whole herds, under conditions of both high and low trypanosomiasis challenge [33,45,[54][55][56][57][58][59][60][61]. The review gave a range of values for the effect of the disease.…”
Section: Parameterising the Cattle Production Systemsmentioning
confidence: 99%